Rifaximin is an effective alternative to metronidazole for the treatment of chronic enteropathy in dogs: a randomised trial. Issue 1 (December 2016) - Menozzi, Alessandro; Dall'Aglio, Manuel; Quintavalla, Fausto; Dallavalle, Luca; Meucci, Valentina; Bertini, Simone
Abstract Background A clinical trial was conducted in order to assess the efficacy of rifaximin, a broad-spectrum antibiotic with negligible gastrointestinal absorption, in comparison with metronidazole, a commonly employed antimicrobial drug, in dogs with chronic enteropathy. Twenty-four pet dogs were randomly enrolled into two different groups: MET group (10 dogs) and RIF group (14 dogs). Dogs of MET group received metronidazole 15 mg/kg q12h for 21 days by oral route, whereas dogs of RIF group, were given rifaximin 25 mg/kg q12h for 21 days by oral route. Clinical signs of disease were evaluated the day before the beginning of drug administration (D0), and at the end of treatment (D21), by means of Canine IBD Activity Index (CIBDAI). Blood levels of C-reactive protein (CRP) at D0 and D21 were also measured, as another parameter of treatment efficacy. The primary outcome measure of efficacy was the complete remission at D21, defined as a 75 % or greater decrease of CIBDAI; secondary outcome measures were the variation of mean CIBDAI scores, of mean CRP serum levels, and any observed adverse effect from D0 to D21. Results Treatment with metronidazole or rifaximin greatly improved the clinical signs of disease in each group: in MET group the complete remission was achieved in 8 of 10 dogs (80.0 %), and partial remission in 2 subjects (20.0 %). In RIF group, 12 of 14 dogs showed complete remission (85.7 %), and the remaining 2 dogs were in partial remission (14.3 %). There were also significant decreases of CIBDAI scores (P  = 0.002 andP  = 0.0002 for MET and RIF, respectively), and CRP levels (P  = 0.002 andP  = 0.0001 for MET and RIF, respectively) compared to pre-treatment values in both groups. No significant difference, however, was found when comparing MET and RIF groups. No relevant side-effect was reported during the trial with either drugs. Conclusions The present study showed, for the first time, that oral rifaximin could represent an effective alternative to metronidazole for the induction of clinical remission in dogs with chronic enteropathy.